Wild boar fat analysis in beef sausage using Fourier Transform Infrared (FTIR Method) Combined with chemometrics - Tengku Nur Indah Sari; Any Guntarti (Faculty of Medicine, Universitas Islam Indonesia, 2018)
Background: Sausage is ready to eat meals for children, adolescents, and older adults. The meat contained in a beef sausage might not be consistent to the one listed on the label. Fourier Transform Infrared (FTIR) spectroscopy combination with a chemometric method is one of the most used methods to detect wild boar fat with rapid and consistent results. Results of analysis can classify fatty acid composition contained. Objective: The aim of this study is to determine the fat profile in sausage samples and differentiate the grouping of wild boar fat and beef fat in sausage preparation. Methods: The study was designed by making 7 different variations of wild boar reference sample concentrations, which were 100%, 75%, 65%, 50%, 35%, 25% and 100% beef. Six other samples were gathered from various street vendors. The results were analyzed using FTIR spectroscopy combined with chemometric with Partial Least Square (PLS) and Principal Component Analysis (PCA). Result: The results of analysis using Horizon MBTM apps showed optimal wave number within 1250-900 cm-1. The results of calibration with equation y= 0.994x + 0.334 and the value of (R2) determination was 0.998, and root mean square error of calibration (RMSEC) was 1.22%. The results of validation using parameter value of root mean square error of cross validation (RMSECV) 2.68%, and root mean square error of prediction (RMSEP) was 0.11%.Conclusion: PCA result showed that five from six samples possibly have same physical and chemical properties similar to fatty beef sausage.